Global longitudinal strain predicts survival and response in patients with systemic AL amyloidosis. analysis of 915 patients from the ALchemy prospective trial. (25th November 2020) - Cohen, O; Ismail, A; Manwani, R; Ravichandran, S; Foard, D; Mahmood, S; Sachchithanantham, S; Martinez-Naharro, A; Fontana, M; Lachmann, H; Hawkins, P; Gillmore, J; et al.
Abstract: Background: Cardiac involvement determines prognosis in systemic AL amyloidosis. The extent is assessed by biomarker-based staging systems. This a prospective report of a large cohort of patients assessing the utility of changes in longitudinal function by 2D strain (GLS%), impairment - a hallmark of amyloidosis. Purpose: To evaluate the prognostic role of GLS% and other echocardiographic parameters in systemic AL amyloidosis. Methods: 915 newly diagnosed patients seen at the UK National Amyloidosis Centre (February 2010–August 2017) were included. All patients underwent 6-monthly comprehensive assessments inclusive of echocardiogram. The European modification of the Mayo 2004 staging was used with Mayo stage III patients stratified into IIIa (NT-proBNP <8500ng/L) and IIIb (NT-proBNP ≥8500ng/L). Results: 653/915 (71.4%) patients had cardiac involvement. Mayo stage 1, 2, 3a and 3b in 144 (15.7%), 302 (33.0%) 344 (37.6%) and 125 (13.7%) respectively. The median NT-proBNP was 2228ng/L and TNT was 0.54ng/ml. The GLS% significantly worsened with increasing Mayo stage (p<0.0001 between GLS% for each Mayo stage). Poorer baseline GLS% associated with significantly worse OS and stratified patients into three groups: GLS% <−12.8%: OS 69.1 months; GLS% −12.8% to −9%: OS 54.5 months; GLS% >−9%: OS 45.3 months (p<0.0001). On univariate analysis, 11/14 parameters predicted survival (LV wall thickness, LV ejection fraction, systolic velocities of the septal (s'sep) and lateral mitral annulus (s' lat), mitral annulus movement at the lateral corner (e' lat), transmitral early peak flow velocity (E) divided by tissue Doppler mitral annular motion velocity (e') – E/e' and mitral annular plane systolic excursion (MAPSE)). Baseline GLS% >−17% was independent of Mayo stage in predicting survival [Mayo II: Hazard ratio (HR) 2.10 (95% CI: 1.12–3.92) p=0.02, Mayo III: HR 3.94 (95% CI: 2.13–7.32) p<0.0001, Mayo IV: HR 7.49 (95% CI: 3.94–14.21) p<0.0001, GLS <17%: HR 2.14 (95% CI: 1.59–2.88) p<0.0001]. At 12 months, only patients in a haematological complete response (CR) had significant improvement in overall GLS% (p=0.02) as well as baso-lateral (p=0.0004) and baso-septal (p=0.0001) GLS% and MAPSE (p=0.002). The OS was significantly better in patients who achieved a minimum absolute improvement in GLS% of 1.5% improvement (not reached in those with improved GLS% vs. 72 mo in those without) (p=0.034)). Conclusion: These data show that baseline GLS% is an independent predictor of survival in AL amyloidosis. GLS% is the first functional marker that is independent of the Mayo staging in predicting outcomes and should be incorporated in prognostic staging for patients with AL amyloidosis. GLS% shows improvement in patients who achieve a complete haematologic response to treatment and improvement in GLS% of 1.5% is associated with improved outcomes. An absolute improvement in GLS% should be considered as a criterion for cardiac response in AL amyloidosis. Funding Acknowledgement: Type of funding source: None